Role of Nitrogen and Iron in Tuber Phenol Content for Resistance to Infection and Better Storability in Bounty-Fertilized Dioscorea Rotundata Variety Oniyere - Otusanya, M. O. (European Journal of Applied Sciences, 2021)
The role of nitrogen and iron in promoting phenol with its antimicrobial properties for disease resistance with implication of better storability of yam tubers is indicated in Dioscorea rotundata variety Oniyere fertilized with an 8-mineral component fertilizer namely Bounty, in this study. The experiment was arranged in RCBD (Randomized Complete Block Design) with 3 treatments and 3 replicates. The treatment was bounty fertilizer at the rate 0, 0.6 and 1.2 ml l-1 applied at 3MAP (months after planting), Tubers were harvested at 6MAP and analyzed for proximate, phenol and mineral content. Another set was incubated with Botryodiplodia theobromae for 2 weeks and then analyzed for phenol and proximate content. Tuber Ca was comparable across treatments, whereas N, S, and Fe were higher in the 0.6 and 1.2 ml l-1 Bounty-fertilized treatments than the control. P was higher only in the 0.6 ml l-1 treatment than the control, whereas K and Mg were higher in the control than the 0.6 ml l-1 treatment and in the 1.2 ml l-1 treatments respectively. Phenol was higher in the 1.2 ml -1 treatment than the control. Calcium which is the second highest (7% w/w) component in Bounty fertilizer was a mean of 14.15 mg/100gdm in Oniyere tubers, which is only 7.73% of phenol content with a mean value of 183.3 mg/100gdm. Calcium also had no significant correlation with phenol. Dry matter and moisture remained unchanged after the incubation, whereas crude fibre and fat increased by 93.6% and 39.47% respectively. Ash increased only in the 1.2 ml l-1 treatment by 22.54% and remained unchanged in the control and 0.6 ml l-1 treatment. Phenol remained unchanged after the incubation in the 0.6 ml l-1 and 0 ml l-1 treatments but decreased in the 1.2 ml l-1 treatment. However carbohydrate and crude protein decreased across the 3 treatments by 2.16% and 51.33% respectively. Correlation of r = -0.5786 between Calcium and moisture indicates Ca will not promote moisture. Positive implication of low moisture for longer tuber storage has been reported. Nitrogen (N) the highest component (15% w/w) of bounty, had significant correlation with phenol and Fe, r = 0.7921 and 0.9840 respectively, thus will enhance production of both tuber phenol and tuber Iron. Fe correlated significantly with S (r = 0.9751) and Fe and S will each in turn promote phenol, r = 0.7629 and 0.7978 respectively. Iron content in Bounty fertilizer is 2% w/w compared to Nitrogen which is 15% w/w, whereas Sulphur is not present in Bounty fertilizer. A future trial should involve analysis of total phenolic compounds (not only phenol), as well as proximate and mineral content, in a longer and time-related incubation of about six to eight weeks, so as to determine all factors contributing to longer and better (quality) storage of variety Oniyere tubers.